ANALYZING THE IMPACT OF URBANIZATION ON ECONOMIC GROWTH AND DEVELOPMENT IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
Urbanization is a transformative process that significantly impacts economic growth and development, particularly in developing countries like India. This paper explores the intricate relationship between urbanization and economic dynamics in India, highlighting both its positive and negative effects. As India experiences rapid urbanization, with projections indicating that over 50% of its population will reside in urban areas by 2031, understanding this phenomenon becomes crucial for policymakers and stakeholders. The positive impacts of urbanization include enhanced productivity, diversification of economic activities, infrastructure development, and improved access to employment and social services. Urban centers, often referred to as engines of economic growth, facilitate innovation, attract investments, and create jobs, ultimately contributing to national GDP. Additionally, urbanization fosters human capital development through better education and healthcare facilities, thereby improving overall living standards.